A novel approach for measuring the vibration properties of non-metallic materials - Sriraman, Shabarish; Goyder, Hugh (University of Liege, 2025)
Non-metallic materials display frequency and temperature dependent dynamic properties which must be characterised for use in computer simulations. The characterisation of such properties is important as most modern structures utilise these materials. Hence, a novel test method has been developed, which combines vibration testing with finite element analysis, to yield dynamic modulus of elasticity and damping. Material properties have been measured in the frequency range 2Hz - 2000Hz. The test method involves a cantilever beam. Two samples of the test material sandwich the root of the beam and are held in place between inertial masses. Experimental modal analysis techniques, where an instrumented hammer vibrates the beam, are used to exercise the material. The modulus of elasticity of the material is found by constructing a finite element model of the test setup and tuning the simulated response with that of the experiment. Damping properties are extracted by applying data fitting techniques to the time histories and spectrum. These are then converted into a material damping property by simulating and accounting for the energy balance between the samples and test setup. Doing so also improves damping simulation accuracy by eliminating the need to estimate Rayleigh damping values at each frequency, as now the material damping property at each frequency can be directly used. For test accuracy, it is important that the sample is gripped in a manner that exercises it effectively and is simple to simulate. Eliminating slipping, and thus the difficult to model friction, is a key concern and has been investigated in depth. The best solution found is an axisymmetric bolting arrangement which holds the samples in place. Additionally, the test setup utilises suspension, together with inertial masses and an orthogonal layout to isolate against external vibrations. Polymers and rubbers, which exhibit complex frequency dependent behaviour, have been reliably characterised using this method. The damping material Sorbothane has also been re-characterised and produced results that aligned with manufacturer specifications. This method proves to be a reliable procedure for dynamic material property testing.
Special issue | 2024 : Special issue on Tribomechadynamics
Keywords: 3403 Macromolecular and Materials Chemistry; 40 Engineering; 34 Chemical Sciences; Non-metallic materials; High frequency testing; Property characterisation method; Damping quantification; Interface stress distribution; Material joints; Non-linear response